2018
DOI: 10.1208/s12249-018-0969-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: In Vitro Characterization and Evaluation of the Cytotoxicity Effects of Nisin and Nisin-Loaded PLA-PEG-PLA Nanoparticles on Gastrointestinal (AGS and KYSE-30), Hepatic (HepG2) and Blood (K562) Cancer Cell Lines

Abstract: The aim of this study was an in vitro evaluation and comparison of the cytotoxic effects of free nisin and nisin-loaded PLA-PEG-PLA nanoparticles on gastrointestinal (AGS and KYSE-30), hepatic (HepG2), and blood (K562) cancer cell lines. To create this novel anti-cancer drug delivery system, the nanoparticles were synthesized and then loaded with nisin. Subsequently, their biocompatibility, ability to enter cells, and physicochemical properties, including formation, size, and shape, were studied using hemolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…The most relevant way to avoid RES recognition is the PEGylation, via masking hydrophobicity of the particles and imparting stealth characteristics by hydrophilic PEG brush (Mansor et al 2018). Experimental research has also proved other favorable properties of PEGylated particles such as reducing aggregation while enhancing stability and biological potency (Goudarzi et al 2018). Moreover, considerable interest has been conducted in the development of ligand coupled NPs like peptide, antibodies, and nucleotides ligands for enhanced localization and active targeting capabilities to specific organs or cells (Dinarvand et al 2011).…”
Section: Pla and Plga Based Mps And Nps Systems For Drug Deliverymentioning
confidence: 99%
“…The most relevant way to avoid RES recognition is the PEGylation, via masking hydrophobicity of the particles and imparting stealth characteristics by hydrophilic PEG brush (Mansor et al 2018). Experimental research has also proved other favorable properties of PEGylated particles such as reducing aggregation while enhancing stability and biological potency (Goudarzi et al 2018). Moreover, considerable interest has been conducted in the development of ligand coupled NPs like peptide, antibodies, and nucleotides ligands for enhanced localization and active targeting capabilities to specific organs or cells (Dinarvand et al 2011).…”
Section: Pla and Plga Based Mps And Nps Systems For Drug Deliverymentioning
confidence: 99%
“…110 Lewies et al 111 showed that when used in combination with conventional chemotherapeutic agents (etoposide, 5-flurouracil, and hydroxyurea), nisin Z has the potential to enhance the cytotoxicity of these chemotherapeutic agents against melanoma cells. Recently, Goudarzi et al 112 demonstrated that nisin-loaded polylactic acid-polyethylene glycol-polylactic…”
Section: Cancermentioning
confidence: 99%
“…Lewies et al showed that when used in combination with conventional chemotherapeutic agents (etoposide, 5‐flurouracil, and hydroxyurea), nisin Z has the potential to enhance the cytotoxicity of these chemotherapeutic agents against melanoma cells. Recently, Goudarzi et al demonstrated that nisin‐loaded polylactic acid‐polyethylene glycol‐polylactic acid nanoparticles exert more potent cytotoxic effects than free nisin on gastrointestinal, hepatic, and leukemia cell lines. Thus, nisin offers great promise as a cancer therapeutic for multiple cancer types.…”
Section: Nisin‐producing Lactococcus Lactis Probiotic and Nisin Are Promising Therapeutics For Oral And Systemic Healthmentioning
confidence: 99%
“…Zone of inhibition were formed between 10.87 to 36.30 mm, depending of solution concentrations from 0.25 ug/mL (10 1 AU/mL) until 2500 g/mL (10 5 AU/mL). This result shows that microorganism was sensitive even when exposed to low nisin concentration, and it is important to establish the relationship between the degree of solubility and pH of nisin in relation to the method used [31]. As it is a soluble peptide with low molecular weight, this facilitates its diffusion and complements its antimicrobial activity [32,33].…”
Section: Nisin Standard Curvementioning
confidence: 99%